Using artificial intelligence to assess clinicians' communication skills. (18th January 2019) - Ryan, Padhraig; Luz, Saturnino; Albert, Pierre; Vogel, Carl; Normand, Charles; Elwyn, Glyn
Abstract : Most doctors have never had their communication skills formally assessed and do not know how they compare with their peers. Glyn Elwyn and colleagues explain how AI might facilitate this and help improve interactions with patients